The role of alkali metal cations and platinum-surface hydroxyl in the alkaline hydrogen evolution reaction - Shah, Aamir Hassan; Zhang, Zisheng; Huang, Zhihong; Wang, Sibo; Zhong, Guangyan; Wan, Chengzhang; Alexandrova, Anastassia N; Huang, Yu; Duan, Xiangfeng (Nature catalysis, 2022)
The platinum-catalysed hydrogen evolution reaction (HER) generally shows poorer kinetics in alkaline electrolyte and represents a key challenge for alkaline water electrolysis. In the presence of alkali metal cations and hydroxyl anions, the electrode–electrolyte (platinum–water) interface in an alkaline electrolyte is far more complex than that in an acidic electrolyte. Here we combine electrochemical impedance spectroscopy and an electrical transport spectroscopy approach to probe and understand the fundamental role of different cations (Li+, Na+ and K+) in HER kinetics. Our integrated studies suggest that the alkali metal cations play an indirect role in modifying the HER kinetics, with the smaller cations being less destabilizing to the hydroxyl adsorbate (OHad) species in the HER potential window, which favours a higher coverage of OHad on the platinum surface. The surface OHad species are highly polar and act as both electronically favoured proton acceptors and geometrically favoured proton donors to promote water dissociation in alkaline media, thus boosting the Volmer-step kinetics and the HER activity.Platinum is the most active catalyst for the hydrogen evolution reaction, but the specific mechanism and the influence of the alkali metal cations remain elusive in alkaline media. Now, electrical transport spectroscopy, electrochemical impedance spectroscopy and ab initio molecular dynamics simulations are combined to elucidate the role of alkali metal cations for this reaction in alkaline electrolyte.